Rome at the cinema: the place experience, between global and local identity - Ricci, Paolo (E|C, 2020)
My article/contribution deals with the link that exists between Rome and cinema in terms of the images of the city and the meaning of space. More specifically, I refer to contemporary film that reflect this. Taking into consideration some typical aspects and analysing others, I have focused on the capital city space in relation to the construction of some of these and in relation to the images that they project, with regards to a wider imagery that becomes international, global and that (almost certainly) dialogues with the characteristics of space and the local context.